2018
DOI: 10.1016/j.jad.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Acute psychoactive effects of intravenous ketamine during treatment of mood disorders: Analysis of the Clinician Administered Dissociative State Scale

Abstract: Introduction: Ketamine has rapid-acting antidepressant effects. Frequently, ketamine administration also causes acute psychoactive effects – in trials, these effects are commonly measured using the Clinician Administered Dissociative State Scale (CADSS). However, the CADSS was not designed for this specific purpose, having been validated in other clinical contexts, and anecdotally does not appear to fully capture ketamine’s acute psychoactive effects. Methods: Data were obtained from 110 individuals with moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 21 publications
1
46
1
2
Order By: Relevance
“…This contrasts with gabapentin and pregabalin, which do not notably cause dissociative effects, disrupt memory nor cause agitation or psychosis in clinical use. Although ketamine (the most widely studied NMDA antagonist for treating pain) is used primarily for perisurgical pain (Kreutzwiser and Tawfic, 2019) and increasingly for treatment-resistant depression (Murrough et al, 2013;van Schalkwyk et al, 2018), it is not used for chronic neuropathic pain (Gilron, 2007), and it has strong psychotomimetic properties (Sos et al, 2013).…”
Section: Analgesia Produced By Gabapentinoids Compared To Known Nmda mentioning
confidence: 99%
“…This contrasts with gabapentin and pregabalin, which do not notably cause dissociative effects, disrupt memory nor cause agitation or psychosis in clinical use. Although ketamine (the most widely studied NMDA antagonist for treating pain) is used primarily for perisurgical pain (Kreutzwiser and Tawfic, 2019) and increasingly for treatment-resistant depression (Murrough et al, 2013;van Schalkwyk et al, 2018), it is not used for chronic neuropathic pain (Gilron, 2007), and it has strong psychotomimetic properties (Sos et al, 2013).…”
Section: Analgesia Produced By Gabapentinoids Compared To Known Nmda mentioning
confidence: 99%
“…There are two frequent effects of ketamine whose potential interrelationship has hardly been investigated: a feeling of lightness/floating in healthy participants and recreational users [1-3], and temporary antidepressant benefits in individuals with treatment-refractory depression [4, 5]. Feelings of lightness/floating are a typical occurrence in psychoactive-substance- or psychologically induced altered states of consciousness [6, 7].…”
mentioning
confidence: 99%
“…There is an inverse relationship between ketamine metabolites and CADSS scores, which may also contribute to sex differences in disassociation symptoms severity [27]. Importantly, the validity of the CADSS for IV ketamine has been criticized as there is no robust association between dissociation symptoms and antidepressive response [28,29]. A systematic review of 60 studies reported that headaches, dizziness, dissociation, and elevated blood pressure were the most frequently reported adverse events of IV ketamine [9].…”
Section: Discussionmentioning
confidence: 99%
“…We used the CADSS as the primary safety instrument to quantify the severity of dissociation. The CADSS was not developed primarily as a safety measure for ketamine treatment and likely underestimates the extent of dissociation experience with ketamine [29]. It should also be recognized that the CADSS was initially developed for dissociative symptoms of PTSD and may not adequately capture the phenomenology of IV ketamine treatment for TRD.…”
Section: Discussionmentioning
confidence: 99%